2020
DOI: 10.3390/buildings10010018
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of 30 Years Outdoor Weathering on the Durability of Hydrophobic Agents Applied on Obernkirchener Sandstones

Abstract: The durability of eleven different water repellents applied on one sandstone type was studied after a long-term weathering at seven different locations in Germany. By measuring colour changes, it could be shown that the formation of black crusts, the deposition of particles and biogenic growth caused a gradual darkening as well as significant changes in total colour over time. Additionally, the water absorption behaviour was investigated with two different methods: applying a low pressure using the pipe method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…1). All locations are characterised by different climatic conditions and emission loads (Orlowsky et al 2020). In addition, specimens were stored in an archive in Bochum, Germany, over the entire period and served as reference.…”
Section: Origin Of the Sample Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). All locations are characterised by different climatic conditions and emission loads (Orlowsky et al 2020). In addition, specimens were stored in an archive in Bochum, Germany, over the entire period and served as reference.…”
Section: Origin Of the Sample Materialsmentioning
confidence: 99%
“…Climatic data and pollutant values on the sites during the last 10 years of exposure can be found in Orlowsky et al (2020). After 2 years a 3 cm thick sample was cut off each prism (Fig.…”
Section: Origin Of the Sample Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 30 years, all the agents show a decrease in performance, but some protective agents still provide an effective hydrophobic layer. Succinctly, the authors [7] concluded that: (i) the protective agents based on isobutyltrimethoxysilane show a clear loss of performance after 2 years of outdoor weathering; (ii) agents containing siloxane, the low-molecular methylethoxysiloxanes, show a good performance, which is similar to, partly better than, that of the oligomer methylethoxysiloxane; (iii) the agents with oligomer siloxane based on an isooctylmethoxy-structure have a higher performance loss than the agents containing low-molecular methylethoxysiloxanes; (iv) after 30 years of outdoor weathering, the effectiveness of the protective agents based on silicone resin is comparable to that of low-molecular siloxanes. Concerning the exposure conditions, the degradation of the treated stones is higher in southern Germany than in North Rhine-Westphalia, mainly due to a longer weathering time of 6 years as well as the rougher environment.…”
mentioning
confidence: 97%
“…Orlowsky et al [7] analysed the durability of 11 different water repellents applied on Obernkirchener Sandstones. The performance of the hydrophobic agents applied is analysed after the samples have been subjected to long-term weathering (30 years of outdoor weathering) in seven different locations in Germany.…”
mentioning
confidence: 99%